Primer for concrete

JP7635523B2Active Publication Date: 2025-02-26DIC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020148148
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-03
Publication Date
2025-02-26
Estimated Expiration
2040-09-03

AI Technical Summary

Benefits of technology

【0008】 本発明のコンクリート用プライマーは、低粘度かつ低臭気で作業性に優れ、硬化性、湿潤面接着性及び耐アルカリ性に優れる塗膜が得られることから、各種コンクリートのプライマーとして、好適に用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635523000001
    Figure 0007635523000001
Patent Text Reader

Abstract

To provide a primer for concrete which has low viscosity, low odor, and excellent workability and gives a coating film excellent in curability, adhesion to a wet surface, and alkali resistance.SOLUTION: The primer for concrete is used which contains: a resin (A) having polymerizable unsaturated groups at both terminals; an unsaturated polyester (B); a (meth)acrylic monomer (C) having a nitrogen atom; a (meth)acrylic monomer (D) having a flash point of 70°C or higher other than the (meth)acrylic monomer (C); and a cyclodextrin derivative (E).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a primer for concrete. [Background technology]

[0002] One of the causes of deterioration of concrete structures is corrosion of the internal rebars caused by the infiltration of rainwater, etc. To address this, methods of protecting the concrete surface with a coating material and preventing spalling by attaching fibers or the like are adopted. The materials used are required to have fast curing properties that allow construction to be completed in a short time, adhesion to concrete that has become wet due to rain, low odor for environmental reasons, etc. As such materials, concrete protection materials containing urethane (meth)acrylate, radical polymerizable monomer, cyclodextrin and / or its derivatives, and unsaturated polyester have been proposed (for example, see Patent Document 1).

[0003] However, this material has a problem of insufficient alkali resistance. Therefore, there has been a demand for a material that has low viscosity, low odor, and excellent workability, and can give a coating film that is excellent in curability, wet surface adhesion, and alkali resistance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-229707 A Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by the present invention is to provide a primer for concrete which has low viscosity, low odor, excellent workability, and gives a coating film which is excellent in curing properties, wet surface adhesion, and alkali resistance. [Means for solving the problem]

[0006] As a result of intensive research by the inventors to solve the above-mentioned problems, they found that the above-mentioned problems can be solved by a concrete primer containing a resin having polymerizable unsaturated groups at both ends, an unsaturated polyester, a (meth)acrylic monomer having a nitrogen atom, a monofunctional (meth)acrylic monomer having a flash point of 70°C or higher, and a cyclodextrin derivative, and thus completed the present invention.

[0007] That is, the present invention provides a primer for concrete, which comprises: (A) a resin having polymerizable unsaturated groups at both ends; (B) an unsaturated polyester; (C) a (meth)acrylic monomer having a nitrogen atom; (D) a (meth)acrylic monomer other than the (meth)acrylic monomer (C) having a flash point of 70°C or higher; and (E) a cyclodextrin derivative. Effect of the Invention

[0008] The concrete primer of the present invention has low viscosity, low odor, and excellent workability, and provides a coating film that is excellent in curing properties, wet surface adhesion, and alkali resistance, and can therefore be suitably used as a primer for various types of concrete. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The concrete primer of the present invention contains a resin (A) having polymerizable unsaturated groups at both ends, an unsaturated polyester (B), a (meth)acrylic monomer having a nitrogen atom (C), a (meth)acrylic monomer other than the (meth)acrylic monomer (C) having a flash point of 70°C or higher (D), and a cyclodextrin derivative (E).

[0010] In the present invention, the term "(meth)acrylic monomer" refers to either or both of an acrylic monomer and a methacrylic monomer, the term "(meth)acrylate" refers to either or both of a methacrylate and an acrylate, and the term "(meth)acryloyl" refers to either or both of an acryloyl and a methacryloyl.

[0011] Examples of the resin (A) having polymerizable unsaturated groups at both ends include epoxy (meth)acrylate, polyester (meth)acrylate, and urethane (meth)acrylate. These resins (A) having polymerizable unsaturated groups at both ends may be used alone or in combination of two or more.

[0012] As the epoxy (meth)acrylate, for example, a compound obtained by reacting a bisphenol type epoxy compound or an epoxy compound obtained by mixing a bisphenol type epoxy compound with a novolac type epoxy compound with an unsaturated monobasic acid by a conventionally known method can be used.

[0013] Examples of the bisphenol type epoxy compound that can be used include a glycidyl ether type epoxy compound having two or more epoxy groups in one molecule obtained by reacting epichlorohydrin with bisphenol A or bisphenol F, a dimethylglycidyl ether type epoxy compound obtained by reacting methylepichlorohydrin with bisphenol A or bisphenol F, and an epoxy compound obtained by reacting an alkylene oxide adduct of bisphenol A with epichlorohydrin or methylepichlorohydrin. These epoxy compounds may be used alone or in combination of two or more.

[0014] As the novolac type epoxy compound, for example, an epoxy compound obtained by reacting phenol novolac or cresol novolac with epichlorohydrin or methyl epichlorohydrin can be used. These epoxy compounds may be used alone or in combination of two or more kinds.

[0015] Examples of the unsaturated monobasic acid that can be used include (meth)acrylic acid, cinnamic acid, crotonic acid, monomethyl maleate, monopropyl maleate, monobutene maleate, sorbic acid, mono(2-ethylhexyl) maleate, etc. These unsaturated monobasic acids may be used alone or in combination of two or more kinds.

[0016] The polyester (meth)acrylate may be, for example, a saturated polyester or an unsaturated polyester having two or more (meth)acryloyl groups in one molecule. The saturated polyester is a product of a condensation reaction between a saturated dibasic acid and a polyhydric alcohol, and the unsaturated polyester is a product of a condensation reaction between an α,β-unsaturated dibasic acid and a polyhydric alcohol, both of which have a (meth)acryloyl group at the end.

[0017] The saturated dibasic acid, α,β-unsaturated dibasic acid and polyhydric alcohol may be the same as those used in the synthesis of the unsaturated polyester (B) described below.

[0018] The polyester (meth)acrylate may be produced by reacting a saturated polyester or an unsaturated polyester with glycidyl (meth)acrylate by a known method.

[0019] As the urethane (meth)acrylate, for example, one obtained by reacting a polyol, a polyisocyanate, and a (meth)acrylic compound having a hydroxyl group or an isocyanate group by a conventionally known method can be used.

[0020] Examples of the polyol that can be used include polyester polyol, polycarbonate polyol, polyether polyol, acrylic polyol, caprolactone polyol, butadiene polyol, etc. These polyols may be used alone or in combination of two or more kinds.

[0021] Examples of the polyisocyanate include aromatic diisocyanates such as phenylene diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, and naphthalene diisocyanate; aliphatic or alicyclic diisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate; and aromatic polyisocyanates such as xylylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, polyphenylene polymethylene polyisocyanate, formalin condensate of methylene diphenyl diisocyanate, and carbodiimide modified product of 4,4'-diphenylmethane diisocyanate. These polyisocyanates may be used alone or in combination of two or more.

[0022] Examples of the (meth)acrylic compound having a hydroxyl group include (meth)acrylic acid alkyl esters having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polyethylene glycol monoacrylate, polypropylene glycol monoacrylate, etc. These compounds may be used alone or in combination of two or more.

[0023] Examples of the (meth)acrylic compound having an isocyanate group that can be used include 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethyloxy)ethyl isocyanate, 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate, etc. These compounds may be used alone or in combination of two or more.

[0024] The number average molecular weight of the resin (A) is preferably 500 to 4,000, since this can further improve workability and curing properties.

[0025] The content of the resin (A) in the primer for concrete is preferably from 10 to 50 mass %, and more preferably from 20 to 40 mass %, since this allows further improvement in curability.

[0026] As the unsaturated polyester (B), for example, one obtained by reacting a dibasic acid including an α,β-unsaturated dibasic acid with a polyhydric alcohol by a conventionally known method can be used.

[0027] Examples of the α,β-unsaturated dibasic acid that can be used include maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, etc. These dibasic acids may be used alone or in combination of two or more kinds.

[0028] As a dibasic acid that can be used other than the α,β-unsaturated dibasic acid, a saturated dibasic acid can be used, for example, phthalic acid, phthalic anhydride, halogenated phthalic anhydride, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, hexahydroterephthalic acid, hexahydroisophthalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, sebacic acid, 1,12-dodecane diacid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid anhydride, 4,4'-biphenyldicarboxylic acid, and dialkyl esters thereof can be used. These dibasic acids can be used alone or in combination of two or more.

[0029] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, neopentyl glycol, hydrogenated bisphenol A, 1,4-butanediol, and alkylene oxide adducts of bisphenol A. Examples of polyhydric alcohols that can be used include 1,2,3,4-tetrahydroxybutane, glycerin, trimethylolpropane, 1,3-propanediol, 1,2-cyclohexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, 1,4-cyclohexanedimethanol, paraxylene glycol, bicyclohexyl-4,4'-diol, 2,6-decalyl glycol, 2,7-decalyl glycol, etc. These polyhydric alcohols may be used alone or in combination of two or more kinds.

[0030] The content of the unsaturated polyester (B) in the primer for concrete is preferably from 1 to 30 mass %, and more preferably from 5 to 20 mass %, since this allows further improvement in curing properties.

[0031] Examples of the (meth)acrylic monomer (C) having a nitrogen atom include (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, isopropyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, diacetone(meth)acrylamide, hydroxyethylacrylamide, and (meth)acryloylmorpholine.

[0032] The content of the (meth)acrylic monomer (C) in the concrete primer is preferably 3 to 50 mass %, more preferably 5 to 40 mass %, and even more preferably 10 to 30 mass %, because this can further improve workability and curing properties.

[0033] Examples of the (meth)acrylic monomer (D) having a flash point of 70° C. or more include (meth)acrylic monomers having an alicyclic structure such as isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; 2-ethylbutyl (meth)acrylate, n-pentyloxyethyl (meth)acrylate, and the like. (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, 3-methylbutyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, neopentyl (meth)acrylate aliphatic (meth)acrylic monomers such as acrylate, hexadecyl (meth)acrylate, and isoamyl (meth)acrylate; (meth)acrylic monomers having ethylene oxide and / or propylene oxide such as 3-methoxybutyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate having an added mole number of oxyethylene in the range of 1 to 15, methoxypolypropylene glycol (meth)acrylate having an added mole number of oxypropylene in the range of 1 to 15, ethoxy-diethylene glycol (meth)acrylate, and ethyl carbitol (meth)acrylate; (meth)acrylic monomers having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate;Aromatic (meth)acrylic monomers such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy polyethylene glycol acrylate, phenyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A, Di(meth)acrylate compounds such as phenol di(meth)acrylate, 1,4-cyclohexanedimethanol di(meth)acrylate, and trimethylolpropane di(meth)acrylate; and polyfunctional (meth)acrylates having three or more functional groups such as trimethylolpropane triacrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate can be used. Among these, (meth)acrylic monomers having a hydroxyl group and (meth)acrylic monomers having ethylene oxide and / or propylene oxide are preferred because they can further suppress odor. These (meth)acrylic monomers may be used alone or in combination of two or more kinds.

[0034] The flash point in the present invention is a value measured by a Seta closed cup flash point measurement.

[0035] The (meth)acrylic monomer ( D The content of ) is preferably from 10 to 70 mass %, more preferably from 20 to 60 mass %, and even more preferably from 30 to 50 mass %, since excellent curability can be achieved with a low viscosity.

[0036] The mass ratio of the (meth)acrylic monomer (C) to the (meth)acrylic monomer (D) ( D / C ) has a better balance of curing properties and wet surface adhesion, so it is recommended to use 95 / 5~ 5 0 / 5It is preferably 0, and more preferably 90 / 10 to 50 / 50.

[0037] Examples of the cyclodextrin derivative (E) include cyclodextrin; alkylated cyclodextrin, acetylated cyclodextrin, and hydroxyalkylated cyclodextrin, in which the hydrogen atom of the hydroxyl group of the glucose unit of cyclodextrin is replaced with another functional group. In addition, any of α-cyclodextrin consisting of 6 glucose units, β-cyclodextrin consisting of 7 glucose units, and γ-cyclodextrin consisting of 8 glucose units can be used as the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives. These cyclodextrin derivatives (E) may be used alone or in combination of two or more kinds. Among these, methylated β-cyclodextrin is preferred because of its excellent solubility in resin.

[0038] The content of the cyclodextrin derivative (E) in the primer for concrete is preferably 0.1 to 5 mass %, more preferably 0.2 to 3 mass %, since the adhesiveness to a wet surface is improved.

[0039] Examples of the silica fine particles (F) include dry silica and wet silica, with dry silica being preferred since it provides a further improvement in thixotropy.

[0040] The average primary particle diameter of the silica fine particles (F) is preferably from 5 to 50 nm, since this further improves thixotropy.

[0041] The silica fine particles (F) preferably have a hydrophobic surface, since this further improves the thixotropy.

[0042] The content of the silica particles (F) in the primer for concrete is preferably from 0.1 to 10 mass %, more preferably from 0.5 to 5 mass %, in view of excellent workability.

[0043] The concrete primer of the present invention contains the resin (A), the unsaturated polyester (B), the (meth)acrylic monomer (C), the (meth)acrylic monomer (D), and the cyclodextrin derivative (E) as essential components, and may contain other additives, etc., as necessary.

[0044] Examples of the other additives include polymerization inhibitors, antioxidants, light stabilizers, solvents, rust inhibitors, sensitizers, leveling agents, rheology control agents, tackifiers, antistatic agents, flame retardant curing agents, curing accelerators, pigments, fillers, reinforcing materials, aggregates, and petroleum waxes.

[0045] The primer for concrete of the present invention can be used as a primer for concrete such as cement concrete, asphalt concrete, mortar concrete, resin concrete, water-permeable concrete, and ALC (Autoclaved Lightweight Aerated Concrete) boards.

[0046] The concrete primer of the present invention has low viscosity, low odor, excellent curing properties, and gives a coating film that has excellent wet adhesion and alkali resistance, and therefore can be suitably used as a primer for various types of concrete. EXAMPLES

[0047] The present invention will be described in more detail below with reference to specific examples. The acid value was measured in accordance with JIS-K-6901, and the average molecular weight was measured under the following GPC measurement conditions.

[0048] [GPC measurement conditions] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 4 mg / mL in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following monodisperse polystyrene.

[0049] (monodisperse polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0050] (Synthesis Example 1: Synthesis of Resin (A-1) Having Polymerizable Unsaturated Groups at Both Ends) A four-neck flask equipped with a thermometer, a stirrer, an inert gas inlet, and a reflux condenser was charged with 1,850 parts by mass of Epicron 850 (manufactured by DIC Corporation), which is an epoxy equivalent obtained by reacting bisphenol A with epichlorohydrin, 860 parts by mass of acrylic acid, 1.36 parts by mass of hydroquinone, and 10.8 parts by mass of triethylamine, and the mixture was heated to 120°C and reacted for 10 hours to obtain a resin (A-1) having polymerizable unsaturated groups at both ends as an epoxy acrylate with a molecular weight of 512 and an acid value of 3.5.

[0051] (Synthesis Example 2: Synthesis of Resin (A-2) Having Polymerizable Unsaturated Groups at Both Ends) A four-neck flask equipped with a thermometer, a stirrer, an inert gas inlet, and a reflux condenser was charged with 250 parts by mass of neopentyl glycol, 100 parts by mass of propylene glycol, 390 parts by mass of adipic acid, and 100 parts by mass of maleic anhydride, and 0.5 parts by mass of monobutyltin oxide was added as an esterification catalyst, and the mixture was reacted for 11 hours at 205° C. Thereafter, the mixture was cooled to 140° C., and then 25 parts by mass of glycidyl methacrylate was added and reacted for 10 hours to obtain a resin (A-2) having polymerizable unsaturated groups at both ends as a polyester (meth)acrylate having a number average molecular weight of 4,150.

[0052] (Synthesis Example 3: Synthesis of Resin (A-3) Having Polymerizable Unsaturated Groups at Both Ends) A reaction vessel equipped with a thermometer, a stirrer, an inert gas inlet, an air inlet and a reflux condenser was charged with 500 parts by mass of polypropylene glycol having a number average molecular weight of 1000 and 172 parts by mass of tolylene diisocyanate, and reacted for 2 hours at 80°C under a nitrogen stream. Since the NCO equivalent was 600, which was almost the theoretical equivalent value, it was cooled to 50°C. Under an air stream, 0.07 parts by mass of hydroquinone was added, and 135 parts by mass of 2-hydroxyethyl methacrylate was added, and the reaction was carried out at 90°C for 4 hours. When the NCO% became 0.1% or less, 0.07 parts by mass of tertiary butyl catechol was added, and a resin (A-3) having polymerizable unsaturated groups at both ends was obtained as a urethane methacrylate having a number average molecular weight of 1,580.

[0053] (Synthesis Example 4: Synthesis of Unsaturated Polyester (B-1)) A reaction vessel equipped with a thermometer, a stirrer, an inert gas inlet, and a reflux condenser was charged with 231 parts by mass of triethylene glycol, 80 parts by mass of diethylene glycol, 102 parts by mass of phthalic anhydride, 210 parts by mass of 3-methyltetrahydrophthalic acid, 0.3 parts by mass of dibutyltin oxide, and 0.1 parts by mass of methylhydroquinone, and reacted for 4 hours at 205° C. The mixture was cooled to 150° C., and 34 parts by mass of maleic anhydride was added and reacted for 4 hours at 190° C. to obtain an unsaturated polyester (B-1) with an acid value of 12.0.

[0054] (Example 1: Preparation and evaluation of concrete primer (1)) In a light-shielding container equipped with a stirrer, a reflux condenser, and a thermometer, 30 parts by mass of a resin (A-1) having polymerizable unsaturated groups at both ends, 10 parts by mass of an unsaturated polyester (B-1), 0.5 parts by mass of methylated β-cyclodextrin, 30 parts by mass of dicyclopentenyloxyethyl methacrylate, 10 parts by mass of 2-hydroxyethyl methacrylate, and 20 parts by mass of acryloylmorpholine were mixed to obtain a concrete primer (1).

[0055] [Viscosity measurement] The viscosity (25°C) of the concrete primer (1) obtained above was measured using a Type i BM viscometer in Table 7 in accordance with "5.5.1 When using the Brookfield type viscometer method" of JIS K6901:2008, and the low viscosity was evaluated according to the following criteria. ○: Less than 400 mPa s ×: 400mPa·s or more

[0056] [Preparation of evaluation samples] 0.25 parts by mass of 8% by mass cobalt octylate, 0.5 parts by mass of a toluidine compound isopropanol solution ("RP-191" manufactured by DH Material Co., Ltd.), and 1 part by mass of a 40% by mass benzoyl peroxide solution were added to and mixed with 50 parts by mass of the concrete primer (1) obtained above to obtain an evaluation sample (1).

[0057] [Evaluation of odor] In an environment of 23°C, the above-obtained evaluation sample (1) was 0.2 kg / m 2 The odor when the paint was applied to a slate board with a brush was evaluated by sensory judgment, and the odor was rated according to the following criteria. ○: No odor or slight odor ×: Odor

[0058] [Evaluation of hardening] The evaluation sample (1) obtained above was placed on a slate board at a pressure of 0.2 kg / m 2 The time until the composition became tack-free when touched with a finger was measured at 23° C., and the curability was evaluated according to the following criteria. ○: Less than 90 minutes ×: 90 minutes or more

[0059] [Evaluation of wet surface adhesion] The evaluation sample (1) obtained above was soaked in water for one day, then taken out and wiped to remove water droplets. 2 The coating was left to cure for one day, and then pulled vertically using a Kenken tensile tester ("Technostar RT-3000LD" manufactured by Sanko Techno Co., Ltd.) to measure the peel strength and evaluate the wet surface adhesion according to the following criteria. 〇1.5N / mm 2 End ×1.5N / mm 2 less than

[0060] [Evaluation of alkali resistance] The evaluation sample (1) obtained above was applied to a mortar measuring 70 x 70 x 20 mm at a rate of 0.2 kg / m using a brush. 2 The specimens obtained by coating were partially immersed in a saturated calcium hydroxide aqueous solution and cured for 30 days at 40°C. After 30 days, the appearance of the specimens was visually observed and the alkali resistance was evaluated according to the following criteria. 〇: No change ×: Blisters or cracks

[0061] (Examples 2 and 3: Preparation and evaluation of concrete primers (2) and (3)) Concrete primers (2) and (3) were prepared in the same manner as in Example 1, except that the resin (A-1) having polymerizable unsaturated groups at both ends used in Example 1 was changed to the resin (A-2) or (A-3) having polymerizable unsaturated groups at both ends, and then their physical properties were evaluated.

[0062] (Example 4: Preparation and evaluation of concrete primer (4)) A concrete primer (4) was prepared in the same manner as in Example 1, except that the resin (A-1) having polymerizable unsaturated groups at both ends used in Example 1 was changed to a resin (A-3) having polymerizable unsaturated groups at both ends, and acryloylmorpholine was changed to diethylacrylamide, and then each physical property was evaluated.

[0063] (Comparative Examples 1 and 2: Preparation and Evaluation of Concrete Primers (R1) and (R2)) Except for using the formulation of Example 1 as shown in Table 1, concrete primers (R1) and (R2) were prepared in the same manner as in Example 1, and then the physical properties were evaluated.

[0064] Table 1 shows the compositions and evaluation results of the concrete primers (1) to (3) and (R1) to (R2) obtained above.

[0065] [Table 1]

[0066] It was confirmed that the concrete primers of the present invention in Examples 1 to 4 have low viscosity, low odor, and excellent workability, and can give coating films that are excellent in curing properties, wet surface adhesion, and alkali resistance.

[0067] Comparative Example 1 is an example that does not contain the unsaturated polyester (B) and the (meth)acrylic monomer, but the viscosity was high and the workability was insufficient.

[0068] Comparative Example 2 is an example that does not contain the nitrogen atom-containing (meth)acrylic monomer (C), but the alkali resistance of the resulting coating film was insufficient.

Claims

1. A primer for concrete comprising (A) a resin having polymerizable unsaturated groups at both ends, (B) an unsaturated polyester, (C) a (meth)acrylic monomer having a nitrogen atom, (D) a (meth)acrylic monomer other than the (meth)acrylic monomer (C) having a flash point of 70°C or higher, and (E) a cyclodextrin derivative, wherein the (meth)acrylic monomer (C) is one or more monomers selected from the group consisting of (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, isopropyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, diacetone(meth)acrylamide, hydroxyethylacrylamide, and (meth)acryloylmorpholine, and the mass ratio (D / C) of the (meth)acrylic monomer (C) to the (meth)acrylic monomer (D) is 95 / 5 to 50 / 50.

2. 2. The primer for concrete according to claim 1, wherein the resin (A) is one or more resins selected from the group consisting of epoxy (meth)acrylates, polyester (meth)acrylates, and urethane (meth)acrylates.

3. 3. The primer for concrete according to claim 1, wherein the content of the (meth)acrylic monomer (C) is 3 to 50 mass %.

Citation Information

Patent Citations

  • Hardenable resin composition, and execution of waterproof agent and resin concrete using the same

    JP2000026558A

  • Radical-polymerizable composition, concrete repair material, and primer for road

    JP2015229707A

  • Curable resin composition, concrete coating composition and lining material

    JP2018009155A

  • Coating for flooring materials and flooring material

    WO2012029155A1

  • Radically polymerizable composition, concrete repair material, and primer for roads

    WO2015186433A1